Prominent entrepreneur traits for income generating programs performance / Norsuhada Sahedan, Norlida Jaafar and Siti Badariah Saiful Nathan - Sahedan, Norsuhada; Jaafar, Norlida; Saiful Nathan, Siti Badariah (UiTM Press, 2018)
Income Generating Program is one of the Malaysian government’s interventions in alleviating urban poverty. Training, motivation, mind development courses and in-kind transfers are provided in the programs productive hard-core and poor individuals to encourage them to participate in entrepreneurship and other income-generating activities that will reduce their poverty. Despite its poverty reduction success, there still remains failure of some programs in achieving the objective of the programs especially in increasing the beneficiaries’ income level. This concept paper has several objectives, a brief description on issues of income generating programs, reviewing the entrepreneur traits which have been found to be prominent in previous studies, i.e., knowledge and skills, motivation, risk taking and passion which have been selected as correlates in the income level.